Pengaruh Model Pembelajaran Meaningful Learning terhadap Peningkatan Pembelajaran Teks Eksplanasi Kelas XI SMAS Muhammadiyah Lempangang - Andi Paida; Anin Asnidar; Irfandi Irfandi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the effect of the Meaningful Learning model on improving students’ learning outcomes in understanding explanatory texts in grade XI of SMAS Muhammadiyah Lempangang. The Meaningful Learning model is a learning approach that emphasizes the connection between new information and the prior knowledge possessed by students, thereby fostering deeper, more relevant, and meaningful learning experiences. This approach is expected to enhance student engagement in the learning process and build logical connections between the concepts being learned. The background of this research stems from the low academic achievement of students in the Indonesian language subject, particularly in understanding explanatory texts. Explanatory texts require logical, systematic, and analytical thinking skills. However, many students score below the Minimum Mastery Criteria (MMC). One of the factors contributing to this low performance is the continued use of conventional teaching methods, such as lectures, which tend to be one-directional and do not actively involve students in the learning process. This research uses a quantitative approach with a quasi-experimental method involving two groups: an experimental group using the Meaningful Learning model and a control group using conventional methods. Data were collected through pretests and posttests and analyzed using a t-test to determine the significance of the difference in learning outcomes between the two groups. The results show a significant improvement in the learning outcomes of students in the experimental group after the application of the Meaningful Learning model. Students became more active, motivated, and capable of better understanding the structure and content of explanatory texts compared to those in the control group. In conclusion, the implementation of the Meaningful Learning model has a positive and significant effect on improving students’ understanding and learning outcomes. This model is recommended as an innovative alternative approach in Indonesian language instruction at the secondary education level to enhance both the quality of the learning process and its outcomes.